2016
DOI: 10.1111/jonm.12369
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a new model of job engagement, psychological empowerment and perceived work environment among Chinese registered nurses at four large university hospitals: implications for nurse managers seeking to enhance nursing retention and quality of

Abstract: For nurse managers wishing to increase nurse engagement and to achieve effective management, both perceived work environment and psychological empowerment are factors that need to be well controlled in the process of nurse administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 33 publications
4
37
0
9
Order By: Relevance
“…The findings corresponded to a qualitative interview study on 27 nurses' commitment to nursing, which showed their professional commitment was the main reason for their retention (Gould & Fontenla, ). Congruent with a study, which specifically focused on the relationship between nurses' intention to remain and occupational commitment, the study also revealed that normative commitment and its associated feelings of obligation and loyalty play an integral part in nurse retention (Engeda, Birhanu, & Alene, ; Fan et al, ; Gambino, ). The results disclosed a significant association between autonomy values and nurses' intention to remain, showing nurses with higher autonomy value were more likely to intend to remain employed.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The findings corresponded to a qualitative interview study on 27 nurses' commitment to nursing, which showed their professional commitment was the main reason for their retention (Gould & Fontenla, ). Congruent with a study, which specifically focused on the relationship between nurses' intention to remain and occupational commitment, the study also revealed that normative commitment and its associated feelings of obligation and loyalty play an integral part in nurse retention (Engeda, Birhanu, & Alene, ; Fan et al, ; Gambino, ). The results disclosed a significant association between autonomy values and nurses' intention to remain, showing nurses with higher autonomy value were more likely to intend to remain employed.…”
Section: Discussionmentioning
confidence: 88%
“…The questionnaire consisted of three parts as follows: Individual characteristics; age, gender, marital status, highest educational level, duration of working as a nurse in this hospital, current position of work, and work department. Work‐related and reinforcing potential predictive factors: these factors were measured using a Likert scale with answers classified in 5 levels from strongly agree to strongly disagree. There were 36 items, which developed from social cognitive theory and previous research studies (Cowden & Cummings, ; Fan et al, ; Goh & Lopez, ; Lee et al, ; Wang et al, ). A question “Will you still work in this hospital until you retire?” was used to identify nurses' intention to remain employed. Likert scale was provided.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No campo da psicossociologia do trabalho (LHUILIER, 2014), o conceito e o objeto engajamento são considerados benéficos para os trabalhadores, ou seja, levam ao bem-estar, uma vez que se considera que trabalhar motivado por fatores ou valores nos quais se acredita faz bem (FAN et al, 2016;JACKSON FILHO, 2015).…”
Section: Engajamento Reconhecimento E Pertencimento No Trabalhounclassified
“…Esse tipo de associação é importante porque boas relações entre enfermeiros e gerentes de enfermagem podem influenciar a atitude geral para com a organização. 7 Além disso, o empoderamento pode contribuir para que os profissionais da enfermagem deixem o quadro de passividade, desmotivação e baixa mobilização, para uma posição ativa, criadora de novos espaços dentro da instituição, mostrando resultados na relação equipe-equipe, equipe-profissional e equipe-comunidade. 8 Existem duas perspectivas de empoderamento no ambiente de trabalho: empoderamento estrutural e empoderamento psicológico.…”
Section: Introductionunclassified